Flexural behavior and design of high-strength I-shaped steel-UHPC composite beams - Lai, Zhichao; Yao, Pengyu; Yang, Xiaoqiang; Li, Shihui; Zhao, Qiu (Advances in structural engineering, 2025)
High-strength materials and corresponding composite members are gradually accepted in the bridge industry to achieve the purposes of large span and lightweight. Three simply supported I-shaped steel-concrete composite beams were tested to investigate their flexural behavior when different combinations of materials were used, i.e., high-strength steel-ultra high performance concrete (HS-UHPC), high-strength steel-conventional strength concrete (HS-CC), and conventional strength steel-ultra high performance concrete (CS-UHPC). The test finds that the HS-UHPC composite beam has the highest flexural strength and reasonable plastic deformation ability as compared to the other two beams. A finite element (FE) model was also constructed and benchmarked. Subsequently, the model was utilized to conduct parametric studies, aimed at exploring in-depth the flexural behavior of steel-concrete composite beams. The results from the tests and FE analyses were employed to assess the suitability of existing design specifications (i.e., AISC 360-22, GB 50017-2017, and Eurocode 4) in estimating the flexural strength of HS-UHPC composite beams. The evaluations indicated that GB 50017-2017 can reasonably estimate the flexural strength of HS-UHPC composite beams. This research provides valuable insights into the design and construction of HS-UHPC composite beams in bridges.